Active site structure and peroxidase activity of oxidatively modified cytochrome c species in complexes with cardiolipin - Capdevila, Daiana Andrea (2015)
We report a resonance Raman and UV-vis characterization of the active site structure of oxidatively modified forms of cytochrome c (Cyt-c) free in solution and in complexes with cardiolipin (CL). The studied post-translational modifications of Cyt-c include methionine sulfoxidation and tyrosine nitration, which lead to altered heme axial ligation and increased peroxidase activity with respect to those of the wild-type protein. In spite of the structural and activity differences between the protein variants free in solution, binding to CL liposomes induces in all cases the formation of a spectroscopically identical bis-His axial coordination conformer that more efficiently promotes lipid peroxidation. The spectroscopic results indicate that the bis-His form is in equilibrium with small amounts of high-spin species, thus suggesting a labile distal His ligand as the basis for the CL-induced increase in enzymatic activity observed for all protein variants. For Cyt-c nitrated at Tyr74 and sulfoxidized at Met80, the measured apparent binding affinities for CL are ∼4 times larger than for wild-type Cyt-c. On the basis of these results, we propose that these post-translational modifications may amplify the pro-apoptotic signal of Cyt-c under oxidative stress conditions at CL concentrations lower than for the unmodified protein.